Efficacy of olokizumab against comorbid depressive disorder in patients with rheumatoid arthritis: Preliminary results of the study - T. A. Lisitsyna; A. A. Abramkin; D. Yu. Veltishchev; O. F. Seravina; O. B. Kovalevskaya; A. B. Borisova; V. G. Ignatiev; E. L. Nasonov (Научно-практическая ревматология, 2023)
Background. Interleukin (IL) 6 plays an important role in the pathogenesis of comorbid rheumatoid arthritis (RA) depression, and IL-6 inhibitors (i) used to treat RA patients may have an antidepressant effect.Objective – to evaluate the effectiveness of Russian iIL-6 olokizumab (OKZ) in reducing symptoms of depression in patients with moderate/high RA activity.Material and methods. To date, 49 RA patients have been included, of which 43 (87.7%) are women, with an average age of 47.8±12.8 years; with a predominant high activity of RA according to DAS28 (CRP) indices (89.8%), SDAI (79.6%) and CDAI (75.5%) and inefficacy of stable 12-week therapy of сDMARDs. In all patients, a psychiatrist, in accordance with ICD-10, diagnosed depression (chronic or recurrent) of varying severity during a semi-structured interview. At week 0, all patients were randomized by the method of sequential numbers in a ratio of 1:1:1 to one of the 3 study groups: group 1 – cDMARDs+OKZ 64 mg subcutaneously once every 4 weeks (n=18); group 2 – cDMARDs+OKZ 64 mg subcutaneously once every 4 weeks + psychopharmacotherapy (PPT) (n=26); group 3 – cDMARDs+PPT (n=5). The duration of the study is 24 weeks. The dynamics of depression severity was assessed on the PHQ-9, MADRS scales; anxiety – HAM-A; experimental psychological projective techniques were also used.Results. After 12 and 24 weeks of therapy, there was a significant decrease in the severity of depression and anxiety in all groups of patients. However, the difference between the final and initial values of all scales was statistically significantly greater (p<0.05) in the groups of patients receiving PPT: cDMARDs+OKZ+PPT (ΔPHQ-9 24–0 =–6.75±3.91; ΔMADRS 24–0 =–22.5±4.83; ΔHAM-A 24-0 =–14.6±5.37) and cDMARDs+PPT (ΔPHQ-9 24–0 =–15.5±3.53; ΔMADRS 24–0 =–25.0±1.41; ΔHAM-A 24-0 =–18.5±3.53), compared with the cDMARDs+OKZ group (ΔPHQ-9 24–0 =–4.00±3.89; ΔMADRS 24-0 =–5.75±8.29; ΔHAM-A 24–0 =–8.50±8.21). According to a semi-structured interview with a psychiatrist and design experimental psychological techniques, the proportion of patients without depression after 24 weeks of therapy was significantly higher in the groups of patients receiving PPT: 90% in the group of cDMARDs+OKZ+PPT and 100% – cDMARDs+PPT, as opposed to 25% in the group of cDMARDs+OKZ. OKZ therapy contributed to the normalization of night sleep but did not lead to a decrease in the frequency and severity of cognitive disorders (CD).Conclusions. OKZ has an antidepressant effect in RA patients, leads to a decrease in the frequency of sleep disorders, but a com[1]plete regression of depression symptoms is possible because of the appointment of OKZ without PPT only in 25% of RA patients, mainly in patients with mild depression. Optimal for the complete regression of depression, anxiety and a decrease in the frequency and severity of CD is a combination of OKZ and PPT.